La letteratura cavalleresca e il mondo arabo: il caso di Andrea da Barberino Regesto e studio critico - Al Owaidi, Rasha (Premio Tesi di Dottorato, 2021)
This work focuses on the research and identification of the existence of Arabic traces, both formal and substantial, within the works of Andrea da Barberino. The critical analysis was based on the elaboration of an exhaustive register of terms of Arabic origin conducted on the six novels attributed with certainty to the author. The survey highlighted the substantial absence of a direct relationship between Barberino and the Arab world, both from the lexical point of view and as regards the mythographic aspects.